Field notes contributed by Hank Zaletel, fall 1986 - Zaletel, Hanket al (1986)
List of birds and locations contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed/flatbed